Pancasila’s Perspective on Dichotomous View between Inspection and Public Service in Immigration Border Control - Agung Purnomo; Wisnu Widayat; Wahyu Eka Putra (International Journal of Religious and Cultural Studies, 2021)
This paper aims to awaken the consciousness of the government and its people towards the importance of the noble values of Pancasila to be implemented in each aspect of life in a nation-state. The dichotomous inspection and public service in Immigration Border Control has undergone inexhaustible which, eventually, putting border controllers into a dilemma when the roles and responsibilities of border control officials as a document examiner or public servant are separated. Many immigration officials in the border are losing the public service spirit and, at the same time, bringing down the sacred meaning of public service. This phenomenon has contributed to the misbehavior and bad decision making which directly impacts the society as service users. Pancasila, as Indonesian ideology, becomes the anti-thesis of positivist/modernist paradigm. It is expected that the spirit of public service by TEGAS will be an alternative solution in the midst of increasingly high public demand for a better border control management.